Melestarikan Kesenian Barong Melalui Motif Batik - Puspitaningtyas, Nana Nilasari (ISI Yogyakarta, 2018)
Indonesia has various regional arts with all forms that have aesthetic valueand are rich in sources of inspiration. Each art gives its own satisfaction to itsaudience. An artist can take advantage of all forms of artistic beauty as the sourceof the idea of creation, such as Barongan Art Blora. As an entertaining regionalperforming arts, figures in Barongan Blora Arts also have a unique and interestingform of visualization. The appeal is the source of the author's idea to be pouredinto a batik motif and applied to a long cloth or jarik cloth with a blend of inlandmotifs namely Batik Truntum Motif and complete with kebaya clothing as hisboss.The creation of this work the author uses two methods, namely theaesthetic approaches and ergonomic approaches. Methods of data collection withliterature study, both from books and google book with scan and copy techniques.The creation method based on Gustami Sp's 3-step 6-step theory, which startsfrom the exploration method, the design of the work, and the realization of thework.Creation of the resulting work is 6 kebaya clothing and 6 pieces of fabricwith the overall model of two pieces. Sihai krah model with Polyester borderfabric material, shantung border and Batik Tulis. The colors used are different butstill matching, the classic colors of Yogyakarta. Classic colors are taken to give agraceful and elegant impression.